2008
DOI: 10.1111/j.1538-7836.2008.03064.x
|View full text |Cite
|
Sign up to set email alerts
|

DU‐176b, a potent and orally active factor Xa inhibitor: in vitro and in vivo pharmacological profiles

Abstract: Summary. Background: Factor Xa (FXa), a key serine protease that converts prothrombin to thrombin in the coagulation cascade, is a promising target enzyme for the prophylaxis and treatment of thromboembolic diseases. DU-176b is a novel antithrombotic agent that directly inhibits FXa activity. Objective: To evaluate the in vitro pharmacological profiles and in vivo effects of DU-176b in animal models of thrombosis and bleeding. Methods: In vitro, FXa inhibition, specificity and anticoagulant activities were exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
210
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(214 citation statements)
references
References 21 publications
1
210
0
3
Order By: Relevance
“…In rat and rabbit thrombosis models, edoxaban dose-dependently inhibited thrombus formation and bleeding time in rats was not significantly prolonged at an antithrombotic dose. A subsequent in vitro study confirmed the concentration-dependent and competitive inhibition of human Factor Xa by edoxaban, without affecting platelet aggregation (Furugohri et al, 2008).…”
Section: Clinical Pharmacologymentioning
confidence: 75%
“…In rat and rabbit thrombosis models, edoxaban dose-dependently inhibited thrombus formation and bleeding time in rats was not significantly prolonged at an antithrombotic dose. A subsequent in vitro study confirmed the concentration-dependent and competitive inhibition of human Factor Xa by edoxaban, without affecting platelet aggregation (Furugohri et al, 2008).…”
Section: Clinical Pharmacologymentioning
confidence: 75%
“…3.4) is a potent, highly selective factor Xa inhibitor with a high affinity for free factor Xa (K i 0.56 nM) and for factor Xa bound to the prothrombinase complex (K i 2.98 nM) [40]. It has predictable and consistent pharmacokinetics with dose proportional increases in plasma concentrations, and a half-life of approximately 10-14 h [10,41,42].…”
Section: Edoxabanmentioning
confidence: 99%
“…This medication should be started 5-10 days after initiation of a parenteral anticoagulant. Similar to rivaroxaban, edoxaban is a selective inhibitor of factor Xa (33,34). The peak plasma concentration is achieved in 1 to 2 hours and steady state is achieved in , major bleeding was defined as: RE-COVER, RE-COVER II, EINSTEIN DVT, EINSTEIN PE, AMPLIFY, HOKUSAI VTE, if it was clinically overt and if it was associated with a fall in the hemoglobin level of at least 20 g per liter, resulted in the need for transfusion of 2 or more units of red cells, involved a critical site, or was fatal; ∑ , clinically relevant non-major bleeding was defined as: RE-COVER, RE-COVER II, AMPLIFY, HOKUSAI VTE, at least one of the following: spontaneous skin hematoma of at least 25 cm 2 , spontaneous nosebleed more than 5 minutes duration, macroscopic hematuria, spontaneous rectal bleeding, gingival bleeding for more than 5 minutes, bleeding leading to hospitalization and/or surgical treatment, bleeding leading to a transfusion of less than 2 units of whole blood or red cells, any other bleeding considered clinically relevant by the investigator; EINSTEIN DVT, EINSTEIN PE, overt bleeding not meeting the criteria for major bleeding but associated with medical intervention, unscheduled contact with a physician, interruption or discontinuation of study treatment, or associated with any other discomfort such as pain or impairment of activities of daily life.…”
Section: Edoxabanmentioning
confidence: 99%